Sejmowe mowy popisowe Kazimierza Nestora Sapiehy. Inspiracje antyczną myślą retoryczną - Gonera, Marzena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The article describes selected poetry by the Pomeranian diplomat Jurga Valentin Winther (1578–1623), which can be included in the inter–genre category of ‘poesis artificiosa’. The works discussed include: anagram, chronogram, acrostic, palindrome, ‘versus concordans’, emblem, labyrinth. The poetic repertoire of Winther clearly shows that while writing, he readily experimented with form, and his searches and innovations sometimes elude genology.